Susceptibility and Resistant of Different Host Varieties of Oil Palm and Coconut Palm towards Pest, Rhinoceros Beetle (Oryctes Rhinoceros) - I, Izaitul Aida; Z, Mohd Rasdi; R, Ismail; M. B, Ismeazilla; K, Mohd Faizol; Z, Muhammad Shakir; A, Nur Fakriyah; S. M, Noor Shuhaina (Asian Journal of Agriculture and Rural Development, 2020)
In the current study, population dynamics of males, females, and total males and females of Rhinoceros Beetle (Oryctes rhinoceros), namely, DXP PPNJ 1 and DXP PPNJ 2, was evaluated in different host varieties of oil palms and coconut palms of Ladang Penyelidikan Segamat in Johor State of Malaysia. Ethyl 4-methyloctanote had been used as a pheromone aggregation in this study. The results clearly indicated that population dynamics of Oryctes Rhinoceros (total male and female) in oil palms and coconut palms has significant difference within the whole sampling period. Based on cumulative Oryctes Rhinoceros caught, varieties of DXP PPNJ 1 and DXP PPNJ 2 had significant effects on its male and female population. MYD inclined more towards the population of Oryctes Rhinoceros male, female and total male and female, giving more impacts, when ccompared with MRD and Tagnanan. Both crops of same species/family were not recommended for planting in that area, because it facees similar problems of direct Oryctes Rhinoceros attacks, obviously affecting the yield. Therefore, MRD and Tagnanan, considered to be a cross-variety, had been recommended to farmers. Instead of having higher yields, farmers have lesser chances of severe attacks by Oryctes Rhinoceros, within the same time period.